1988
DOI: 10.1093/mutage/3.6.485
|View full text |Cite
|
Sign up to set email alerts
|

Studies of an S9-based metabolic activation system used in the mouse lymphoma L5178Y cell mutation assay

Abstract: The purpose of this work was to define, in this laboratory, the conditions of most general utility for the metabolic activation of chemicals to mutagens in the mouse lymphoma L5178Y cell tk+tk- ----tk-tk- assay. The approach used was to optimize the generation of non-toxic concentrations of NADPH from NADP glucose-6-phosphate (G6P) and G6P dehydrogenase, then use that system to examine the effects of increasing concentrations of Aroclor-1254-induced Fischer 344 male rat liver post-mitochondrial supernatant flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 0 publications
0
6
2
Order By: Relevance
“…Other investigators [McGregor et al, 1985[McGregor et al, , 1988Novak et al, 1985;Oberly et al, 1989;Tregerman et al, 19881 Although the widiely used exogenous activation system reported by Clive and Spector [I9751 in the mouse lymphoma assay is capable of metabolizing many promutagens to an active form, our studies indicate that it does not sustain NADPH production throughout the hr exposure.…”
contrasting
confidence: 52%
“…Other investigators [McGregor et al, 1985[McGregor et al, , 1988Novak et al, 1985;Oberly et al, 1989;Tregerman et al, 19881 Although the widiely used exogenous activation system reported by Clive and Spector [I9751 in the mouse lymphoma assay is capable of metabolizing many promutagens to an active form, our studies indicate that it does not sustain NADPH production throughout the hr exposure.…”
contrasting
confidence: 52%
“…Although these concentrations are much higher then those generally used for rat S-9 systems [e.g., McGregor et al, 1988;Majeska and Matheson, 1990;Paolini et al, 19901, we saw no evidence of cytotoxicity or increases in background SCE or Abs when compared with the 1 mM NADP and 5.8 mM isocitrate we use in our routine rat S-9 system.…”
Section: Discussioncontrasting
confidence: 57%
“…The Panel considered that the methods implemented were sufficiently robust to support the results reported, but not adequate for the present evaluation, because the endpoint used was not relevant for the mechanism of action of non-radiomimetic chemical compounds. McGregor et al (1988) aimed to define the optimal conditions for the metabolic activation of chemicals to mutagens in the L5178Y/TK+/-Mouse Lymphoma Assay using different pro-mutagenic compounds. Methanol was assessed for its mutagenicity at 5-50 μL/mL (approximately 3.95-39.5 mg/mL).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Overall judgement: The methods implemented were thought not to be sufficiently robust to support the results reported. Ref: McGregor et al (1985McGregor et al ( , 1988 Saccharomyces cerevisiae (ATCC26422)…”
Section: Negative B)mentioning
confidence: 99%